Chloroplast genome structure and phylogenetic position of Lophatherum gracile. Issue 1 (2nd January 2021) - Zhou, Caibi; Zhou, Xiaolu; Dai, Tingrui; Wen, Zhirui; Guo, Xiying; Song, Yuyan; Long, Lu; Li, Yaling; Mei, Xin
Abstract: Lophatherum gracile is distributed in south China, Japan and South Asia, and it is wild in the valley, stream, woodland, forest edge and gully edge. In this study, the complete chloroplast genome sequence of Lophatherum gracile was successfully obtained using Illumina sequencing. The full length of the chloroplast genome length was 137, 749 bp with a typical quadripartite structure: one large single copy (LSC) region (80, 610 bp), one small single copy (SSC) region (12, 429 bp), and a pair of inverted repeats (IRs) (22, 355 bp each). The GC content of this genome was 38.64%. The whole genome contained 130 genes, including 85 protein-coding genes, 37 tRNA genes, and 8 rRNA genes. Phylogenetic analysis indicated that Lophatherum gracile was closely related to Cenchrus americanus and Cenchrus longispinus .